Omalizumab, the first available antibody for biological treatment of severe asthma: more than a decade of real-life effectiveness - Corrado Pelaia (Therapeutic Advances in Respiratory Disease, 2018)
Omalizumab was the first, and for a long time the only available monoclonal antibody for the add-on treatment of severe allergic asthma. In particular, omalizumab selectively targets human immunoglobulin (Ig)E, forming small-size immune complexes that inhibit IgE binding to its high- and low-affinity receptors. Therefore, omalizumab effectively blunts the immune response in atopic asthmatic patients, thus significantly improving the control of asthma symptoms and successfully preventing disease exacerbations. These very positive effects of omalizumab make it possible to drastically decrease both referrals to the emergency room and hospitalizations for asthma exacerbations. Such important therapeutic actions of omalizumab have been documented by several randomized clinical trials, and especially by more than 10 years of real-life experience in daily clinical practice. Omalizumab can also interfere with airway remodelling by inhibiting the activation of IgE receptors located on structural cells such as bronchial epithelial cells and airway smooth muscle cells. Moreover, omalizumab is characterized by a very good safety and tolerability profile. Hence, omalizumab represents a valuable therapeutic option for the add-on biological treatment of severe allergic asthma.